Recent Advances in Electrochemistry for the Synthesis of N-Heterocycles - Sbei, Najoua; Listratova, Anna V.; Titov, Alexander A.; Voskressensky, Leonid G. (Synthesis, 2019)
The construction of N-heterocyclic rings represents a very important and fast-developing area of organic synthesis. In this context, electrochemistry has emerged as a mild solution for generating in situ the required electrophilic substrates, bases and nucleophiles derived from low-level and extremely stable reagents, the further application of which makes some heterocycles more accessible. In this review, we have covered the recent advances in the electrochemical synthesis of five- and six-membered N-heterocyclic compounds published from 2017 to October 2018.1 Introduction2 Electrochemical Synthesis of Five-Membered N-Containing Heterocycles2.1 Pyrrolidines2.2 Imidazoles2.3 Pyrazoles2.4 Triazoles2.5 Oxazoles2.6 Indoles2.7 Thiazoless3 Electrochemical Synthesis of Six-Membered N-Containing Heterocycles3.1 Piperidines and Pyridines3.2 Quinazolinones3.3 Benzoxazines4 Conclusions
Keywords: azine; azole; direct and indirect electrolysis; N-containing heterocycles